2013
DOI: 10.4236/apd.2013.22007
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of discourse improvement with dopaminergic medication

Abstract: Dopaminergic therapy can improve motor functioning in Parkinson's Disease (PD), but its effect on spoken discourse is poorly understood. This study addressed whether discourse produced during a one-minute monologue would be affected by medication withdrawal. We performed a detailed analysis of semistructured speech samples in 38 patients with PD, including measures of efficiency, syntactic complexity, cohesion (i.e., lexical and grammatical ties between sentences), and coherence (i.e., semantic relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Global coherence has been used as a measure to understand the differences between macroversus microlinguistic processing, as a means to explore potential cognitive and linguistic contributions to discourse, and as a way of tracking progress in treatment and recovery. The 4-point and 5-point GC scales have been used to analyze the spoken discourse patterns of a number of different clinical and non-brain-injured populations (e.g., Cahana-Amitay & Jenkins, 2018;Coelho & Flewellyn, 2003;Coelho et al, 2012;Gola et al, 2015;Hough & Barrow, 2003;Kurczek & Duff, 2011Laine et al, 1998;Lê et al, 2014;Rogalski et al, 2010;Rogalski & Edmonds, 2008;Sanchez & Spencer, 2013;Van Leer & Turkstra, 1999;Wright & Capilouto, 2012;Wright et al, 2013;Wright et al, 2014). The current study provides preliminary evidence of external validity for the 4-point GC scale.…”
Section: The Clinical Utility Of the Gc Scalesmentioning
confidence: 60%
“…Global coherence has been used as a measure to understand the differences between macroversus microlinguistic processing, as a means to explore potential cognitive and linguistic contributions to discourse, and as a way of tracking progress in treatment and recovery. The 4-point and 5-point GC scales have been used to analyze the spoken discourse patterns of a number of different clinical and non-brain-injured populations (e.g., Cahana-Amitay & Jenkins, 2018;Coelho & Flewellyn, 2003;Coelho et al, 2012;Gola et al, 2015;Hough & Barrow, 2003;Kurczek & Duff, 2011Laine et al, 1998;Lê et al, 2014;Rogalski et al, 2010;Rogalski & Edmonds, 2008;Sanchez & Spencer, 2013;Van Leer & Turkstra, 1999;Wright & Capilouto, 2012;Wright et al, 2013;Wright et al, 2014). The current study provides preliminary evidence of external validity for the 4-point GC scale.…”
Section: The Clinical Utility Of the Gc Scalesmentioning
confidence: 60%
“…As a first step in further understanding the nature and impact of PD on expressive language, we examined the discourse of a convenience sample of individuals with PD in the early stages of the disease. A previous study of discourse among individuals with PD found that that discourse production was more efficient and coherent when on medication vs. off medication [25]. The study highlighted that the cognitive resources supporting expressive language could be impacted by the disease even in the earliest disease stage.…”
Section: Discourse Coherencementioning
confidence: 71%
“…Additional insights may have been learned by also collecting data during the "on" medication state. Sanchez and Spencer (2013) found individuals with PD produced more efficient and coherent discourse when "on" medication versus "off" medication [25]. Third, although PD participants were all at H & Y stages 2 -3, the average disease duration for the sample was greater than 4 years.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation